THE EFFECT OF ENERGY DRINKS ON THE DIGESTIVE SYSTEM - Ruzmetova Shaxnoza Davronbekovna (Scholar Express Journals, 2024)
Consumption of energy drinks has been increasing dramatically in the last decades, particularly amongst adolescents and young adults. Energy drinks are aggressively marketed with the claim that these products give an energy boost to improve physical and cognitive performance. However, several adverse health effects have been related to energy drink, this has raised the question of whether these beverages are safe?! This review will carry out to identify and discuss the articles that examined the beneficial and adverse health effects related to energy drink. Although energy drink may have beneficial effects on physical performance, these products also have clear deleterious health consequences
Keywords: energy drinks; adverse effects; energy boosts; caffeine